Emotional Intelligence, Emotional Labor and Job Performance: Does Employer Ownership Matter? - Evidence from China - Ma, S.; Silva, M.; Trigo, V. (15th EBES Conference, 2015)
Research on the relationship between emotional intelligence and job performance is mixed, and the topic has been under researched in the context of China. Our study contributes to the literature by exploring Chinese employed adults’ emotional intelligence in relationship to emotional labor and job performance across different type of employment organizations, including foreign enterprises, Chinese private enterprises and Chinese government-back organizations. Participants in this study were 306 managers and professionals in the China mainland. The results show that there was a significant difference in emotional labor over the three employer ownerships. Specifically, respondents working in Chinese private enterprises reported the highest level of emotional labor, while those working in governmental institutions lower levels of emotional labor. Moreover, the overall sample analyses indicated that EI has no significant effect on in-role performance while the emotional labor has significant effect on in-role performance, suggesting that emotional labor but not EI are valid predictors of work performance in Chinese context.Moreover, emotional labor is a moderator in the relationship between EI and job performance. When examining the above relationship in the above three different employer ownerships, similar result of the overall sample was found for the sample of governmental institutions, but not for foreign enterprise and Chinese private enterprise. In other words, for the latter two employer ownerships, neither emotional intelligence nor emotional labor is valid predictors of work performance. The paper discusses these findings with reference to previous research in the context of the particular characteristics of organizations operating in China, and taking into consideration the impact of a changing economic and social environment on Chinese adults in their workplaces.